2018
DOI: 10.1097/md.0000000000010701
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between foot posture and dental malocclusions in children aged 6 to 9 years

Abstract: The aim of this study was to determine the association, if any, between foot posture and dental malocclusions in the anteroposterior plane, in children.The study population consisted of 189 children (95 boys and 94 girls) aged 6 to 9 years. In every case, previous informed consent was requested and obtained from the parent/guardian and the study was approved by the Ethics Committee of the University of Málaga (CEUMA 26/2015H).This observational, descriptive, cross-sectional analysis is based on a study populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 40 publications
1
16
0
1
Order By: Relevance
“…There are various studies that attempt to show the relationship between the Stomatognathic Apparatus and the postural system through the different muscle chains (1)(2)(3). Some hypotheses suggest a relationship in both the cranial-caudal direction as well as the podo-cranial direction, therefore malocclusion and its treatments may influence body posture, contact between the foot and the ground, center of mass, footprint, and vice-versa, although it is a controversial topic among the scientific community (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…There are various studies that attempt to show the relationship between the Stomatognathic Apparatus and the postural system through the different muscle chains (1)(2)(3). Some hypotheses suggest a relationship in both the cranial-caudal direction as well as the podo-cranial direction, therefore malocclusion and its treatments may influence body posture, contact between the foot and the ground, center of mass, footprint, and vice-versa, although it is a controversial topic among the scientific community (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Studies demonstrate that breathing, the position of the head, the neck, moods, and anxiety can modify posture [ 16 , 17 , 18 , 19 ]. Those authors who mean to demonstrate the correlation between the distinct body segments base themselves on the hypothesis that any functional alteration of the oral cavity, which involves an alteration of the biomechanics of the temporomandibular articulation (TMJ), produces an alteration of the functions of masticatory muscles, which can be transmitted to all the distal muscles through muscle chains [ 20 , 21 ]. This transmission through the muscle chains brings about alterations of the cervical muscles, producing changes in all the planes of the spinal column’s space at this level, provoking descending compensations at both the dorsal and the lumbar level.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship is associated with various studies that show that pronation of the foot causes an internal rotation of the tibia, which is accompanied by an internal rotation of the femur, an anteriorization of the pelvis, and the consequent structural changes in the spine. This is termed by some authors as the global pronation of the complete global limb [ 23 , 24 ] and, therefore, dysfunctions in the way the upper arches and lower arches interrelate (which is known as dental occlusion) and consequently alter craniofacial growth and its development are of great importance in the establishment or severity of dentomaxillary abnormalities [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This showed that patients with a class III malocclusion had a tendency to lean in the posterior direction. 50 The reason for the backward sway in class III malocclusion group and a forward sway in the class II malocclusion group can be explained through the chain theory. According to this theory, the entire body system is divided into 3 rings.…”
Section: Malocclusion and Body Posturementioning
confidence: 99%